2016
DOI: 10.1159/000452263
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Preoperative Prognostic Nutritional Index in Epithelial Ovarian Cancer Patients Treated with Platinum-Based Chemotherapy

Abstract: Background: The aim of present study was to investigate the role of the prognostic nutritional index (PNI) used as a prognostic marker for predicting response and survival outcomes in patients with epithelial ovarian cancer (EOC) who are receiving platinum-based chemotherapy. Patients and Methods: Patients with a new diagnosis of EOC receiving postoperative platinum-based chemotherapy were identified. The PNI was calculated as 10 × serum albumin value (g/dl) + 0.005 × peripheral lymphocyte count (per mm3<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 26 publications
1
38
0
1
Order By: Relevance
“…Petefészekrákban (n = 344), a műtét előtti PNI<45 rövidebb progressziómentes (HR 1,890 [95%-os CI 1,396-2,560], p<0,001) és teljes túléléssel (HR 1,747 [95%-os CI 1,293-2,360], p<0,001) társult [24]. [25].…”
Section: Eredményekunclassified
“…Petefészekrákban (n = 344), a műtét előtti PNI<45 rövidebb progressziómentes (HR 1,890 [95%-os CI 1,396-2,560], p<0,001) és teljes túléléssel (HR 1,747 [95%-os CI 1,293-2,360], p<0,001) társult [24]. [25].…”
Section: Eredményekunclassified
“…This result suggested that the use of PNI in cases of recurrences would more likely reflect the sensitivity to treatment rather than predict the time to recurrence. Previously, Miao et al reported that PNI was useful for predicting platinum resistance in ovarian cancer and was an independent prognostic factor for OS and progression-free survival 21 neutrophil-to-lymphocyte ratio (NLR) at recurrence increased to the same level as preoperative NLR in case of recurrence of OCCC 7 . NLR, as well as PNI, is known as a marker that reflects systemic inflammatory status.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 articles were selected for full review, as shown in Figure 1. Six articles were excluded for various reasons, leading to the final inclusion of five articles for study [10][11][12][13]16]. Table 1 summarizes the characteristics of the five included studies.…”
Section: Selection Processmentioning
confidence: 99%
“…However, evidence of the significance of the PNI in OC is controversial. A retrospective study by Feng et al [10] on 875 OC patients revealed null results between preoperative PNI and overall survival (OS) of OC, in contrast to other studies that showed a significant association [11][12][13]. Interestingly, a systematic review and meta-analysis in 2019 by Wang et al [14] showed significant association of the PNI with the prognosis of patients with gynecological cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation